The Change of the Auditor Towards The Big Four Auditing Firms in Mexico - Toscano Moctezuma, Juan Alfonso (2018)
In this paper, we present the results of an empirical study which analyzes the reasons why some companies with certain corporate characteristics, after having changed their external auditor, choose one of the Big Four auditing firms in Mexico. For this purpose, we have estimated a logistic regression model, using an observable sample of 972 annual reports, belonging to a total of 135 companies listed on the Mexican Stock Exchange, during the period from 2000 to 2007.